ACCOUNTING APPLICATION FOR CONSTRUCTION GOODS PROCUREMENT RECORDING (CASE STUDY PT. PLN (PERSERO) UPT CIREBON) - Widya Jati Lestari; Agus Sevtiana; Alitia Rachmawati (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
PT. PLN (Persero) UPT Cirebon is a state-owned company that takes care of the electricity aspects in ULTG Cirebon, Garut, Ciamis, and Jatibarang. Inventories of existing materials in this is not for resale. Inventories of existing materials at PT. PLN (Persero) UPT Cirebon is shown to support in carrying out operational programs and investment programs to generate or generate electricity. In this electricity company, there are problems and obstacles in recording the procurement of construction goods, because there are some activities that still use the manual system. To assist the power company in managing information in recording the procurement of construction goods so that it can be searched more quickly and accurately, it must have a system that can be used to help solve existing problems. This research produces a Construction Goods Procurement Recording Application that can manage any required information. The reports generated from this application are Material Mutation Data, Contract Letters for Routine SPPL and Non-routine SPPL, Proof of Cash Out and Cash Disbursement Journal. System procedures that apply in PT. PLN UPT Cirebon includes related parts, internal control system, and documents used. The analysis and system design stages are described manually using a flowchart accompanied by an explanatory narration, then computerized into context diagrams, relationship diagrams between entities, and relationships between tables used. After this stage is complete, the next stage is the design of the software system. The design uses Visual Basic 6.0 as the programming language and Microsoft Access 2003 as the database.